Duszpasterstwo Kościoła w Polsce wobec postępującego pluralizmu społeczno-kulturowego - Przybecki, Adam (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
The progressive social and cultural pluralism in Poland remains a significant challenge for the pastoral work of the Church. Its origins could already be seen in the late 1970s, when Poland was still under the leadership of the Communist Party. The article discusses the ongoing process of social and cultural pluralism and the consequences that result from it, for the pastoral ministry of the Church in Poland. The author tries to describe this process and then introduces the main thoughts of the Church's teaching regarding the phenomenon in question. At the end, he formulates proposals that can become an impulse for Polish pastoral ministry.